Pengaruh Job Demand, Burnout, dan Job Satisfaction terhadap Turnover Intention Pegawai di PT. Telkomsel - Alexander Marcel Putra Perdana; I Nyoman Sutapa (Jurnal Titra, 2021)
In company, a high turnover rate will have negative impact such as emergence of recruitment cost, training cost and decrease the productivity rate. Every company must take notice on some aspect like job demand, burnout, and employee’s job satisfaction. Based on employee interview, in PT. Telkomsel, there are many people following the early retirement program. He also said that he is exhausted at work. Therefore, this observation aims to find out whether there is an effect between job demand and turnover intention through burnout and job satisfaction. This research was done by distributing a questionnaire to 76 employees. After all data was collected, observer will analyze descriptively and test some hypothesis with Structural Equation Modelling method to know the impact between those variable. The results of the study stated that job demand had no significant effect on turnover intention, but burnout and job satisfaction were able to become mediating variables because both had a significant effect on turnover intention. In addition, job demand has a significant effect on burnout and job satisfaction.This research can be useful for the company to decreases the turnover intention rate.